CO2 gasification and pyrolysis reactivity evaluation of oil shale - Tang, Luyao; Yan, Yuxin; Meng, Yang; Wang, Jiayu; Jiang, Peng; Pang, Cheng Heng; Wu, Tao (Elsevier, 2019)
This research focuses on the non-isothermal CO2 gasification and pyrolysis reactivity via thermogravimetric analysis. It was found that CO2 decreased activation energy of all four types of oil shale (Fushun, Jinzhou, Wulin, Xingsheng). Activation energy of XS oil shale was highly reduced from 59.86 kJ/mol to 9.48 kJ/mol. Reactivity index results showed that WL and XS oil shales were observed to be more dependent on CO2 atmosphere. Alkali metal oxide also contributed to thermal decomposition according to thermogravimetric (TG) and differential thermal analysis (DTG) curves during CO2 gasification process. Overall, CO2 atmosphere can be used to improve oil shale decomposition, especially for alkali- rich shales, while providing an efficient and effective means to convert greenhouse gases into useful fuels. © 2019 The Authors. Published by Elsevier Ltd. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/) Peer-review under responsibility of the scientific committee of ICAE2018 - The 10th International Conference on Applied Energy.